(untitled) (Universal International Scientific Journal, 2026)
Today, it is known that the incidence of oncological diseases is increasing among the population. One of these diseases is liver cancer. Liver cancer occupies one of the leading places in the world in terms of oncological mortality. Liver cancer remains a serious health problem in Uzbekistan. According to WHO data (2020), the mortality rate from this disease reached 1,194 people, which is 0.74% of the total mortality in the country. At the same time, secondary (metastatic) tumors that spread from other organs are diagnosed more often than primary cancer. The main risk factors are viral hepatitis B and C, alcoholic liver disease, non-alcoholic fatty liver disease (NAFLD), cirrhosis, and exposure to carcinogens. Hereditary factors and chronic stress also play an important role in the development of this pathology. The article reviews modern approaches to primary, secondary, and tertiary prevention of liver cancer, as well as the role of early diagnosis and interdisciplinary collaboration.